Research Management Seminar - Said, Ibrahim (NIL, 1987)
Prof Diraja Ungku Aziz will be the session IV chairman to the research management seminar. The Organizing Committee of Research Management Seminar express their sincere gratitude to Prof Diraja Ungku Aziz.